Evaluation of the Fracture Resistance of Roots Obturated with Bioceramic-Based Root Canal Sealer and Two Different Techniques - İpek Eraslan Akyüz; Hüseyin Sinan Topçuoğlu; Salih Düzgün (Current Research in Dental Sciences)
Objective: The aim of this study was to evaluate the fracture resistance (FR) of the teeth that had been filled using two different root canal-filling techniques and root canal sealers.Methods: Ninety single-rooted lower premolars, extracted for periodontal reasons, were selected. The crowns of the teeth were removed with diamond saw to obtain a root length of 13 mm. The working length of the teeth, excluding the negative control group, was advanced until the number 10 K-file inserted into the root canal was visible through the apical orifice, and the working length was measured to be 1 mm less than the visible length. The teeth were divided into 6 different groups (n=15). Group 1: unprepared and unfilled (negative control), Group 2: prepared and unfilled (positive control): Group 3: prepared and filled with Ceraseal (CS) + Single Cone Technique (SCT), Group 4: prepared and CS + Cold Lateral Compaction Technique (CLCT), Group 5: prepared and filled with AH Plus Jet (AHPJ) + SCT, Group 6: prepared and filled with AHPJ + CLCT. Vertical force was applied to the universal test machine until fracture occurred, and the maximum force required to fracture was recorded. Results: The Positive control group had significantly less FR than other groups, while the negative control group had significantly more FR than other groups (P.05). Conclusions: There was no significant difference between root canal-filling sealer and techniques.